Alkaline metal reagent-assisted synthesis of monodisperse iron oxide nanostructures - Lee, Kwan; Lee, Sangyeob; Oh, Min Chul; Ahn, Byungmin (Metals, 2018)
The solvothermal decomposition of iron complexes using the heat-up process enables monodisperse Fe3 O4 nanoparticle synthesis. Here, we demonstrate that the high reduction potential capability of alkaline metal reagents in the reductive environment allows for pure magnetite phase formation at 200◦ C, which is lower than that of typical synthetic method and offers highly crystalline superparamagnetic and ferrimagnetic nanostructures with the ability to control uniformity including spherical and cubic morphology with narrow size distributions. Our method involved reduction of the acetylacetonate and acetate anions to aldehyde and alcohol as an oxygen resource for iron oxide nucleation in an inert condition. For confirming the developed pure surface phase of alkaline metal reagent-assisted magnetite nanoparticle, the magnetic field-dependent shifting of blocking temperature was investigated. The degree of the exchange interaction between core spins and disordered surface spins is attributed to the ratio of core spins and disordered surface spins. The decrease in disordered surface spins deviation due to an enhanced pure phase of magnetite nanoparticles exhibited the negligible shift of the blocking temperature under differently applied external field, and it demonstrated that alkaline metal reagent-induced reductive conditions enable less formation of both disordered surface spins and biphasic nanostructures.
Keywords: Alkaline metals; Blocking temperatures; Iron oxide; Magnetic nanoparticles; Superparamagnetic; Surface anisotropy; Surface disordered spins